2004
DOI: 10.1002/ajh.20196
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profile of sickle cell disease in Oman

Abstract: The aim of our study was to assess the cytokine profile of sickle cell disease (SCD) patients in steady state and in vaso-occlusive crisis (VOC). VOC has a complex nature, involving interactions between sickle red blood cells (RBC), the endothelium, and leucocytes. Endothelial damage due to recurrent adhesion of sickle RBCs may disrupt endothelial function, leading to altered cytokine release. It is therefore pertinent to study the cytokine profile of SCD patients in steady state and in crisis prior to explori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
117
4
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(143 citation statements)
references
References 33 publications
(35 reference statements)
17
117
4
5
Order By: Relevance
“…The same group (Bao et al, 2013) also presented data suggesting that regulatory B cells (Bregs) from alloimmunized and non-alloimmunized SCD patients differ in their ability to produce IL10 upon stimulation and dampen monocyte activation despite comparable frequencies of Bregs (CD19 + CD24 hi CD38 hi and CD24 hi CD27 + subsets) supporting an altered immunoregulatory state in alloimmunized SCD patients. Investigations of cytokine levels during acute SCD-related complications have shown increased neutrophil chemotaxis, monocyte phagocytosis and levels of IL6 and TNF during VOC (Graido-Gonzalez et al, 1998;Pathare et al, 2004). Additionally, circulating and bronchoalveolar lavage fluid levels of IL8 are elevated in SCD patients with ACS compared to SCD patients at steady state and non-SCD patients (Abboud et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The same group (Bao et al, 2013) also presented data suggesting that regulatory B cells (Bregs) from alloimmunized and non-alloimmunized SCD patients differ in their ability to produce IL10 upon stimulation and dampen monocyte activation despite comparable frequencies of Bregs (CD19 + CD24 hi CD38 hi and CD24 hi CD27 + subsets) supporting an altered immunoregulatory state in alloimmunized SCD patients. Investigations of cytokine levels during acute SCD-related complications have shown increased neutrophil chemotaxis, monocyte phagocytosis and levels of IL6 and TNF during VOC (Graido-Gonzalez et al, 1998;Pathare et al, 2004). Additionally, circulating and bronchoalveolar lavage fluid levels of IL8 are elevated in SCD patients with ACS compared to SCD patients at steady state and non-SCD patients (Abboud et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Others, however, have found a small but significant elevation in circulating IFN-␥ levels in steady-state SCD individuals [16]. In contrast to the lack of alteration in circulating IFN-␥ in our population of steady-state patients, we found IFN-␥ mRNA expression to be increased significantly in the neutrophils of these individuals compared with control individuals; previous studies have also demonstrated that SCD lymphocytes, when cultured in the presence of activating phytohemagglutinin, produce significantly higher levels of IFN-␥ than control lym- phocytes [28].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of elevated inflammatory biomarkers during sickle cell pain crisis are consistent with previous studies showing elevated neutrophil count and CRP in steady state with further elevation during pain crisis, though we did not observe an elevated neutrophil count in steady state compared with healthy individuals as previously reported. 13,14 The observational nature of this study does not allow us to causally link inflammation with increased oxygen consumption; however, these data emphasize the relevance of inflammation to the pathophysiology of sickle cell disease, especially during pain crisis. …”
mentioning
confidence: 95%